2020
DOI: 10.1089/whr.2020.0034
|View full text |Cite
|
Sign up to set email alerts
|

Rural–Urban Residence and Stroke Risk and Severity in Postmenopausal Women: The Women's Health Initiative

Abstract: Background: The impact of rural-urban residence on stroke risk and poor stroke outcomes among postmenopausal women is unknown. Methods: We used data from the Women's Health Initiative (WHI) (1993-2014; n = 155,186) to test the hypothesis that women who live in rural compared with urban areas have higher stroke risk and worse stroke outcomes than urban women. We used rural-urban commuting area codes to categorize geocoded participant addresses into urban, large rural, or small rural areas. Incident strokes duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(52 reference statements)
0
1
1
Order By: Relevance
“…Huang et al stated that high-strain jobs are correlated with an increased risk of stroke [ 45 ]. In addition, despite the fact that residence has a low impact as a risk factor in stroke in our study, Sealy-Jefferson et al concluded that postmenopausal women who lived in rural areas had a higher stroke risk [ 46 ]. Gender presents differences in stroke rates among women and men [ 3 ].…”
Section: Discussioncontrasting
confidence: 63%
“…Huang et al stated that high-strain jobs are correlated with an increased risk of stroke [ 45 ]. In addition, despite the fact that residence has a low impact as a risk factor in stroke in our study, Sealy-Jefferson et al concluded that postmenopausal women who lived in rural areas had a higher stroke risk [ 46 ]. Gender presents differences in stroke rates among women and men [ 3 ].…”
Section: Discussioncontrasting
confidence: 63%
“…2 A trend for increased risk among women living in small rural areas in the United States was observed in one study. 3 In China, the stroke incidence was double in the North compared with the South of the country, and this difference was driven entirely by rural dwellers. This was postulated to be explained by hypertension differences among North and South residents.…”
Section: Rural Versus Urbanmentioning
confidence: 99%